A zero-waste concept of multifunctional clothing design / Mohammad Shafirul Riza Ibharim and Rosita Mohd Tajuddin - Ibharim, Mohammad Shafirul Riza; Mohd Tajuddin, Rosita (Universiti Teknologi Mara Cawangan Pulau Pinang, 2021)
In the rapid development of technology and infrastructure, fashion has moved forward in producing the current style and trend known as fast fashion. The accessible and affordable fashion enables consumers to have varieties of choices that turn into over- consumption. The clothing industry is known as the second- highest polluting industry in the use of materials, and this has given a negative impact on the environment. The research aims to design a range of multifunctional clothing that has both added and creative values, which can be transformed into multiple usages, styles, and looks. Elements such as flexibility, functionality, and user-friendliness are applied to convert clothes into different types of garments that are suitable to be worn in different situations and purposes. The research found that the application of the zero-waste concept would improve the functional features, which could sustain the garment worn for a long period. The final product fulfilled the elements and characteristics of multifunctional clothing with the design projected to achieve the objective of the zero-waste concept based on recovery, reuse and recycle. The convertible designs are suitable for daily wear activities that have an evergreen look that follows the current trend and style.